School-Based 4-H Programming Series: Designing Programs Based on Time Involvement - Vanessa Spero (EDIS)
One of the biggest factors to consider when starting a school-based program is the amount of time and level of commitment that can be provided for the 4-H program at that site. This new 5-page document discusses the degree of commitment, intensity, and Positive Youth Development (PYD) impact of the program. The most PYD-intensive program will include a model for sustainability. Sustainable programs will ultimately survive and thrive without continual supervision and daily maintenance. Written by Vanessa Spero-Swingle and published by the UF/IFAS 4-H Youth Development Program. https://edis.ifas.ufl.edu/4h406